Pengaruh Disiplin dan Lingkungan Kerja Terhadap Kinerja Karyawan di Hotel Puri Saron Senggigi Lombok Barat - Aditama, I Wayan Induyoga; Kartimin, I Wayan (Jurnal Mosaik Hospitaliti, 2022)
This study aims to determine the partial and simultaneous influence of discipline and work environment on employee performance at Puri Saron Senggigi Hotel. The respondents used in this study were 42 permanent employees at Puri Saron Senggigi Hotel. The data used is premier data derived from the questionnaire. The questionnaire was tested using the validity and reliability method, the test continued with classical assumption test and the hypothesis was proven using multiple linear regression analysis processed by the SPSS (Statistical Package for Social Science) version 22. The result showed that discipline and work environment partially influence employee performance at Puri Saron Senggigi Hotel. The result of analysis for the discipline variable obtained a 2,311 value of t-arithmetic > t-table value 2,02269 with a 0,026 significance value and the result of analysis for the discipline variable obtained an 11,146 value of t-arithmetic > t-table value 2,02269 with 0,000 significance value, meaning the hypothesis was accepted and confirmed the existence of a positive. The result for the discipline and work environment have a 62, 599 f-count value > f-table value 3,23 with 0,000 significance value, then there is a positive and significant effect between discipline and work environment on employee performance at Puri Saron Senggigi Hotel.